METHODS OF TEACHING ISLAMIC FIQH - Muhammad Jarir (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
This paper examined the most important methods used in the teaching of Islamic fiqh at the university level. The paper identified two types of methods and highlighted their advantages and disadvantages. The study particularly highlighted the Islamic perception of the methods and the optimal characteristics of a fiqh instructor. The paper concluded with a number of suggestion and recommendation that’s my correct the course of university teaching of Islamic fiqh. The paper mainly calls for the need to diagnose the causes of students’ weaknesses in this field and to find solutions to these causes.Copyright © 2013 by Al-Ta'lim All right reservedDOI: 10.15548/jt.v20i2.36